Espectroscopia Mössbauer : condições experimentais de aquisição e estocagem multicanal para a análise numérica de dados com adequação de resolução espectral - Shigeyosi, Willian Takemitsu (Universidade Federal de São Carlos, 2012)
The objective of this work is to examine the use of Mossbauer spectroscopy in two aspects: the data acquisition, using four different setups and their analysis, comparing three different fittings programs. Concerning to acquisition, we showed that the adaptation of the Ortec MCS-32 system acquisition, to use not just 512 channels but as well 1024, 2048 and 4096 channels can improve the spectra quality. However, the time acquisition increases, proportionally to the increase of channels number. Four different samples were used in these tests, whose data were acquired using 512, 1024, 2048 and 4096 channels. The first and second samples analyzed, were two clay from Sta. Gertrudes region in São Paulo´s state -BR which had been treated in different conditions. Although the spectra resolution was better, in this case, we showed that the results quality are similar, independently of the channels number. The third one was pellet of iron ore, produced by Cia. Vale do Rio Doce . In this case, the use of 2048 channels data was suitable to identify a structure, not observed when less channels were used. It was propitiate as well by the fitting through the WinNormos for Igor. At last, we re-analyzed some spectra, acquired using 512 channels, from a previous study of our research group, on the AISI 316L stainless steel, applying the WinNormos for Igor. The spectra were fitted using the site plus field distribution model , conducting to better identification of the phases and their percent in the samples. The study and comparison of the three PC fitting programs showed that the WinNormos for Igor, is the most appropriate because its use is very simple, and permits much more flexibility on the fittings, making possible distribution on the different sensible parameters on the function used in the fitting.
Keywords: Física nuclear; Espectroscopia de Mössbauer; Ajuste gaussiano; Aço inoxidável; Minérios; Espectroscopia de alta resolução; CIENCIAS EXATAS E DA TERRA::FISICA